How does policy focus influence scientific research? - Kishi, Naoko (Science & public policy, 2020)
Policy focus gives scientists an incentive to pursue specific research subjects and influences a trend of scientific research. This study examines how public grant is allocated for stem cell research in Japan and shows that scientists are likely to advance their research toward the direction led by policy. Since Japanese scientists discovered a method to generate induced pluripotent stem cell (iPSC) in 2006, public financial and institutional support has skewed toward iPSC. The 2012 Nobel Prize in Physiology or Medicine for iPSC has also had an impact on policy and scientists’ selection of stem cells. Scientists in the top universities are likely to select iPSC research. In addition, iPSC research obtains more amount of public grant funding than other stem cell research. However, scientists’ age has no relevant impact on selecting iPSC research. Finally, this study concludes that targeted public funding skews knowledge portfolio by scientists in a nascent field.